2018
DOI: 10.1002/wrna.1510
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic RNA modification 5‐methylcytosine and its emerging role as an epitranscriptomic mark

Abstract: It is a well‐known fact that RNA is the target of a plethora of modifications which currently amount to over a hundred. The vast majority of these modifications was observed in the two most abundant classes of RNA, rRNA and tRNA. With the recent advance in mapping technologies, modifications have been discovered also in mRNA and in less abundant non‐coding RNA species. These developments have sparked renewed interest in elucidating the nature and functions of those “epitransciptomic” modifications in RNA. N6‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
228
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(229 citation statements)
references
References 144 publications
(286 reference statements)
0
228
0
1
Order By: Relevance
“…NSUN-1 is also a member of the NOP2/Sun RNA methyltransferase family. Since there are only two known m 5 C residues on worm 26S rRNA (Sharma and Lafontaine, 2015; Trixl and Lusser, 2019), one of them at C2381, being installed by NSUN-5, we speculated that NSUN-1 might be required for introducing the second m 5 C residue at position C2982. Notably, both 26S m 5 C sites are localized close to important functional regions of the ribosome, and they are highly conserved during evolution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NSUN-1 is also a member of the NOP2/Sun RNA methyltransferase family. Since there are only two known m 5 C residues on worm 26S rRNA (Sharma and Lafontaine, 2015; Trixl and Lusser, 2019), one of them at C2381, being installed by NSUN-5, we speculated that NSUN-1 might be required for introducing the second m 5 C residue at position C2982. Notably, both 26S m 5 C sites are localized close to important functional regions of the ribosome, and they are highly conserved during evolution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The merits of using bsRNA-seq to discover m 5 C sites transcriptome-wide have been controversially discussed (Legrand et al 2017;Linder and Jaffrey 2019;Motorin and Helm 2019;Trixl and Lusser 2019). We contend that the bsRNA-seq approach as presented here is fit-for-purpose as it is based on a combination of efficient bisulfite reaction conditions, bespoke read mapping and conservative site calling from replicate data.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome-wide m 5 C maps at variable depth are by now available for several tissues and cell lines of human/mouse (Squires et al 2012;Hussain et al 2013b;Khoddami and Cairns 2013;Blanco et al 2016;Amort et al 2017;Legrand et al 2017;Yang et al 2017;Wei et al 2018;Chen et al 2019;Huang et al 2019;Sun et al 2019), zebrafish (Yang et al 2019b), plant (Cui et al 2017;David et al 2017;Yang et al 2019a), archaeal (Edelheit et al 2013) and even viral (Courtney et al 2019a;Courtney et al 2019b) origin, persistently identifying sites with biased distribution in mRNAs and/or ncRNAs, reviewed in (Trixl and Lusser 2019). Several studies have further suggested regulatory roles for m 5 C in mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome-wide m 5 C maps at variable depth are by now available for several tissues and cell lines of human/ mouse [9,37,[45][46][47][48][49][50][56][57][58][59], zebrafish [51], plant [60][61][62], archaeal [63], and even viral [64,65] origin, persistently identifying sites with biased distribution in mRNAs and/or ncRNAs, reviewed in [66]. Several studies have further suggested regulatory roles for m 5 C in mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Imperfections of each method have been noted, for example, in m 5 C-RIP, antibody specificity is crucial, while for miCLIP and Aza-IP, sensitivity might not reach lower abundance targets. All this can account for inconsistencies in site detection across different methods [10,66]. bsRNAseq is not completely specific to m 5 C (e.g.…”
Section: Introductionmentioning
confidence: 99%